(untitled) (Cadernos ESP, 2023)
The COVID-19 pandemic transformed health and the sanitary context in Ceará, causing the publication of state decrees. Objective: to verify how many decrees published in Ceará between March 16, 2020 and April 30, 2022 had the item “Health Protection Measures” with health penalties from Federal Law No. 6437/1977 in a complementary and supplementary way. Method: descriptive-analytical, quantitative approach, documentary analysis of the State Decrees of the State of Ceará. Results: 95 state decrees published, 77 with “Health protection measures”, 47 in 2020, 40 in 2021 and 8 in 2022, 3 concurrent and supplementary penalties to Federal Law nº 6437/1977. Conclusion: The decrees in Ceará with health protection measures strengthened and gave autonomy to the actions of Health Surveillance and collective health in the fight against COVID-19.